2013
DOI: 10.5713/ajas.2012.12303
|View full text |Cite
|
Sign up to set email alerts
|

Improving Productive and Reproductive Performance of Holstein Dairy Cows through Dry Period Management

Abstract: To determine the effects of dry period (DP) length on milk yield, milk composition, some blood metabolites, complete blood count (CBC), body weight and score and follicular status, twenty five primiparous and multiparous Holstein cows were assigned to a completely randomized design with DP-60 (n = 13) and DP-20 (n = 12) dry period lengths. Cows in the DP-60 produced more milk, protein, SNF, serum non-esterified fatty acids (NEFA) and beta hydroxyl butyrate acid (BHBA) compared with cows in DP-20 (p≤0.05). Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Previous studies (e.g., Klusmeyer et al, 2009;Soleimani et al, 2010;Safa et al, 2013) have shown that reducing the dry period length decreases milk yield in the subsequent lactation. This has been also confirmed by retrospective studies (Atashi et al, 2013;Ghavi Hossein-Zadeh and Mohit, 2013;Steeneveld et al, 2013).…”
Section: Milk Productionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies (e.g., Klusmeyer et al, 2009;Soleimani et al, 2010;Safa et al, 2013) have shown that reducing the dry period length decreases milk yield in the subsequent lactation. This has been also confirmed by retrospective studies (Atashi et al, 2013;Ghavi Hossein-Zadeh and Mohit, 2013;Steeneveld et al, 2013).…”
Section: Milk Productionmentioning
confidence: 94%
“…Most previous studies (e.g., Rastani et al, 2005;Pezeshki et al, 2007;Soleimani et al, 2012) found no effect of shortening the dry period to shorter than 40 d on basic parameters of blood, such as concentrations of glucose, BHBA, and NEFA. Watters et al (2008), Klusmeyer et al (2009), and Safa et al (2013) observed decreased concentrations of BHBA and NEFA after calving for cows with SDP compared with cows given the traditional dry period of about 60 d. As reviewed by Pezeshki et al (2010), continuously milked cows have lower concentrations of BHBA and better energy status in the subsequent lactation.…”
Section: Concentrations Of Plasma Metabolites and Parameters Of Rumen Fluidmentioning
confidence: 95%
“…Dry period is one of the important management strategies. Previous studies reported that to maximize milk yield in the next lactation in dairy cows, a 50 to 60 d dry period is necessary (Safa et al 2013). Reducing dry period length may affect fertility efficiency (Watters et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mammary involution and growth occur during the NLP and the rate of this process is an important factor for milk production efficiency in the subsequent lactation. Previous studies have shown that reducing the NLP length decreases milk yield in the subsequent lactation (Klusmeyer et al, 2009;Soleimani et al, 2010;Safa et al, 2013). This has also been proven in retrospective reports (Atashi et al, 2013;GhaviHossein-Zadeh and Mohit, 2013;Steeneveld et al, 2013).…”
Section: Discussionmentioning
confidence: 59%